Recovery and distribution of supplied nitrogen to young grapevines - Brunetto, Gustavo; Kaminski, João; Melo, George Wellington de; Santos, Danilo Rheinheimer dos (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to estimate the recovery and the distribution of N supplied to young grapevines. The experiment was carried out in greenhouse at Embrapa Uva e Vinho, Bento Gonçalves, RS, Southern Brazil. Cultivars used were Riesling Itálico and Chardonnay grafted on rootstock 101-14 Mgt. One plant was cultivated in each vase containing 3.5 kg of Udorthent soil. The solution of ammonium sulphate with 2% atoms 15N, at the rate of 185.60 mg N, was applied on the soil surface after the transplantation of the grapevines. Plants were collected six times, during vegetative growth, and fractionated in leaves, rootstock + scion, thick roots and fine roots, and then oven-dried, weighted, and analyzed for total N and 15N contents. The largest N recovery of the fertilizer for the young grapevines ocurred in times near to the N supplying. The largest amount of N accumulated in the grapevines was derived from different forms of the N supplied. Leaves and roots were the largest compartment of total N and N fertilizer.